MODEL ANTECEDENTS AND CONSEQUENCES OF DRIVING DONATION - M. Anissul Fata; Eman Sulaiman; Erwan Iskandar (Journal Of Resource Management, Economics And Business, 2023)
Purpose: This literature review aims to synthesize existing models and theories on the antecedents and consequences of driving donation behavior, particularly within the context of digital and technological advancements in nonprofit fundraising. Research Methodology: This study employs a qualitative literature review approach, analyzing peer-reviewed journal articles, books, and reports to map the psychological, sociocultural, technological, and organizational factors influencing donation behavior. The review integrates theoretical perspectives including social exchange theory, behavioral economics, and cultural frameworks. Results: Findings reveal that emotional appeal, transparency, personalization, technological integration (such as AI, mobile platforms, and blockchain), and cultural sensitivity significantly influence donor intentions and behaviors. Moreover, reciprocal communication and social proof through digital platforms enhance donor trust and sustained engagement. Consequences include increased donor loyalty, organizational credibility, and more effective fundraising outcomes. Limitations: This review is limited by its reliance on secondary data, which may not fully capture emerging real-time donor behavior trends. Future empirical studies are needed to validate and extend the findings across diverse sociocultural contexts. Contribution: The study offers a comprehensive conceptual framework to guide nonprofit organizations in designing effective, culturally attuned, and technology-driven donation strategies. It also identifies gaps in literature, paving the way for future research in behavioral and technological dimensions of charitable giving.